Marist School integrated information literacy program (MaSInform program) A study on the integration of library lessons and information literacy skills in a school's curriculum based on the fully integrated collaborative model of integrated curriculum - Evangelista, Dia Marie P. (2018)
In the age where information can be accessed anywhere and anytime, information literacy skills are more vital than ever. These skills can be best learned in schools and universities. This is the primary reason why librarians have assumed a new role of equipping pupils with these skills. However, information literacy skills cannot be taught and learned effectively in isolation. These skills will be meaningful and essential if taught together with subjects or lessons related to them. The integration of library instruction in the curriculum can only be effective if librarians and teachers work together.